1974
DOI: 10.1161/01.str.5.6.775
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acute Stroke on Cardiac Functions as Observed in an Intensive Stroke Care Unit

Abstract: Fifty-two stroke patients, 43 with cerebral ischemia and nine with cerebral hemorrhage, underwent continuous cardiac monitoring in an Intensive Stroke Care Unit shortly after the onset of the acute cerebrovascular accident. In the group of patients with no evidence of pre-existing heart disease, eight of 18 with cerebral ischemia and five of seven with hemorrhage developed ECG abnormalities. Additional ECG changes were noted in 21 of 25 patients with cerebral ischemia and two of two with hemorrhage who were kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0
2

Year Published

1975
1975
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(56 citation statements)
references
References 34 publications
4
50
0
2
Order By: Relevance
“…We speculate that parasympathetic tone was diminished ipsilateral to the affected hemisphere associated with a reciprocal rise in sympathetic tone on that side and recommend that a prospective study be undertaken to test this hypothesis more definitively. 9 -10 which exceeds that among control subjects. 11 To date, the mechanisms that could account for these changes have not been well understood, but a primary focus has been on increased sympathetic tone, 12 " 16 perhaps through disinhibition of hypothalamic or other autonomic regulatory centers.…”
Section: Background and Purposementioning
confidence: 72%
“…We speculate that parasympathetic tone was diminished ipsilateral to the affected hemisphere associated with a reciprocal rise in sympathetic tone on that side and recommend that a prospective study be undertaken to test this hypothesis more definitively. 9 -10 which exceeds that among control subjects. 11 To date, the mechanisms that could account for these changes have not been well understood, but a primary focus has been on increased sympathetic tone, 12 " 16 perhaps through disinhibition of hypothalamic or other autonomic regulatory centers.…”
Section: Background and Purposementioning
confidence: 72%
“…[15][16][17][18][19][20] The incidence rate of arrhythmias was reported in these studies with a remarkable high fluctuation, ranging from 31% to 87% of all patients. A number of factors may be responsible for the reported discrepancies: conflicting definition of arrhythmias as well as different techniques, duration, and different evaluation of cardiac monitoring.…”
Section: Incidence Of Serious Tachycardia and Bradycardiamentioning
confidence: 92%
“…In some studies, the diagnosis of stroke was established clinically in absence of CT scanning, because modern imaging techniques have not been generally available yet. 16,19 In addition, sinus tachycardia or isolated premature ventricular or supraventricular beats were reported as significant arrhythmia. However, recommendations on the treatment of asymptomatic premature beats have meanwhile been modified and urgent therapeutic intervention is no longer indicated in the majority of cases.…”
Section: Incidence Of Serious Tachycardia and Bradycardiamentioning
confidence: 99%
“…One early study found that 67% of patients admitted to an intensive care stroke unit developed conduction or rhythm abnormalities on 24-hour monitoring, however this was a small study and included both ischemic and hemorrhagic strokes. 14 In a more recent larger study, ECG abnormalities were observed in 60% of patients with cerebral infarction. 15 In multivariate analyses of these patients, 3-month mortality was predicted by AF, atrioventricular block, ST-changes, and inverted T-waves independent of stroke severity, prestroke disability, and age.…”
Section: Telemetry Monitoringmentioning
confidence: 90%